Will AI Enable Universal Healthcare Access? A Critical Examination of Digital Health Equity - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Will AI Enable Universal Healthcare Access? A Critical Examination of Digital Health Equity The promise of Artificial Intelligence (AI) in healthcare is...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics